Investigating the Factors Influencing Employee Performance - Deddy Novie Citra Arta; Syamsu Rijal; Harun Samsudin; I Nyoman Tri Sutaguna (International Journal of Economics and Management Research, 2023)
This study aims to analyze the influence of Leadership Style, Motivation and Work Discipline on the Performance of Government Apparatuses in Cicendo District, Bandung City. This study involved 63 Cicendo District government officials, Bandung City, and all of them became respondents using a multiple linear regression analysis model. The results of this study indicate that Leadership Style, Motivation and Work Discipline simultaneously have a positive and significant influence on the performance of Cicendo District Government Apparatuses, Bandung City. While partially it was found that the leadership style factor had the most dominant significant influence on the performance of the Cicendo District Government Apparatus, Bandung City.